2017
DOI: 10.3389/fnagi.2017.00218
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Post-stroke Depression: A Meta-analysis

Abstract: Background: Stroke not only impacts patients physically but also economically. Post-stroke depression (PSD), as a common complication of stroke, always obstructs the process of stroke rehabilitation. Accordingly, defining the risk factors associated with PSD has extraordinary importance. Although there have been many studies investigating the risk factors for PSD, the results are inconsistent.Objectives: The objectives of this study were to identify the risk factors for PSD by evidence-based medicine.Data sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
160
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(185 citation statements)
references
References 97 publications
13
160
0
12
Order By: Relevance
“…Depression is experienced by 33 % of patients after a stroke [8]. Our large sample size and collection of many confounding variables allowed us to confirm that our results were unaffected even after removing stroke patients and those with migraines from our analysis.…”
Section: Discussionmentioning
confidence: 52%
“…Depression is experienced by 33 % of patients after a stroke [8]. Our large sample size and collection of many confounding variables allowed us to confirm that our results were unaffected even after removing stroke patients and those with migraines from our analysis.…”
Section: Discussionmentioning
confidence: 52%
“…Finally, findings of this study add to an increasing body of literature showing that physical limitations and disability are important contributors to mental health in patients recovering from a stroke. For instance, a recent meta-analysis demonstrated that severity of stroke and level of handicap were important predictors of post-stroke depression (Shi et al, 2017). In addition, a study comparing patients after stroke and myocardial infarction reported that the higher incidence of depression after stroke could be attributed to the higher level of handicap following stroke (Aben et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…В ряде работ показано, что тревожно-депрессивные нарушения более выражены в пожилом возрасте [21]. Другие авторы сообщают, что в острой стадии инсульта тревожно-депрессивные нарушения, напротив, чаще отмечаются у молодых пациентов [22]. Противоречивы сведения и о связи тревожно-депрессивных симптомов постинсультной депрессии и пола.…”
Section: факторы риска развития тревожно-депрессивных нарушенийunclassified
“…В то же время есть данные, что депрессия у мужчин протекает тяжелее и реже регрессирует. Предположительно, мужчины психологически хуже адаптируются к утрате трудоспособности, что приводит к более выраженным эмоциональным нарушениям [22,23]. К депрессии после инсульта предрасполагают некоторые особенности семейного положения, а именно вдовство, развод или одинокий образ жизни [21].…”
Section: факторы риска развития тревожно-депрессивных нарушенийunclassified